2016
DOI: 10.1111/jcpe.12616
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of adjunctive anti‐plaque chemical agents: a systematic review and network meta‐analyses of the Turesky modification of the Quigley and Hein plaque index

Abstract: Within the limitations of this study (including the severe imbalance in the amount of evidence), dentifrices containing triclosan-copolymer or chlorhexidine and mouthrinses containing essential oils or chlorhexidine showed the greatest effect on PlI scores as assessed with NMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
71
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 69 publications
5
71
0
6
Order By: Relevance
“…However, in the present study, the individuals in the periodontitis group underwent full-mouth scaling plus CHX, as described by Quirynen et al 25 , instead of EO. Despite some undesirable side effects due to its higher anti-plaque effectiveness, CHX is the first option for the short-term chemical dental biofilm control of periodontitis 14,[26][27][28][29] . Thus, whether a longer period of time is needed to observe the total protein level reduction in the presence of periodontitis is a subject for further studies, especially when considering the improvements in the classical clinical parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the present study, the individuals in the periodontitis group underwent full-mouth scaling plus CHX, as described by Quirynen et al 25 , instead of EO. Despite some undesirable side effects due to its higher anti-plaque effectiveness, CHX is the first option for the short-term chemical dental biofilm control of periodontitis 14,[26][27][28][29] . Thus, whether a longer period of time is needed to observe the total protein level reduction in the presence of periodontitis is a subject for further studies, especially when considering the improvements in the classical clinical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this group received oral hygiene instructions and rinsed with an EO mouthwash, which, according to Raslan et al 13 , provided additional benefits when compared to isolated mechanical procedures. Studies that have compared EOs with CHX demonstrated that EOs are a viable option for gingivitis patients due to their appropriate clinical benefits with less side effects 14,[26][27][28][29] . The present gingivitis patients showed statistically significant improvements at 3 months, as revealed by the PD, PI, and GI reductions.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason to explain the discrepancy between both reviews could be that, in the previous one, only two studies assessing the outcomes of interest were included . Nevertheless, when these products have been evaluated for the reduction of plaque and gingivitis indices during a 6‐month period, two recent systematic reviews have failed to support an added value …”
Section: Discussionmentioning
confidence: 99%
“…The dentifrices without BS were separated into negative and positive controls. As a positive control, dentifrices containing stannous fluoride (SnF) or triclosan (Tcs) as ingredients were considered . All the other dentifrices without BS were considered as negative controls.…”
Section: Methodsmentioning
confidence: 99%